2010
DOI: 10.1097/acm.0b013e3181ccc96f
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Longitudinal Mentored Scholarly Project: An Approach at Two Medical Schools

Abstract: An increasing number of medical schools have implemented or are considering implementing scholarly activity programs as part of their undergraduate medical curricula. The goal of these programs is to foster students' analytical skills, enhance their self-directed learning and their oral and written communication skills, and ultimately to train better physicians. In this article, the authors describe the approach to implementing scholarly activities at a school that requires this activity and at a school where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 5 publications
0
75
0
2
Order By: Relevance
“…Alternatively, an institution may opt for a step-wise approach: the research elective model may prove useful in pilot-testing the research program's suitability for their institution, and in allowing time to build and consolidate various elective courses before making the commitment to a full, school-wide research requirement. Several successful programs have shown that such an approach can be beneficial 3 .…”
Section: Innovations In Pharmacymentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, an institution may opt for a step-wise approach: the research elective model may prove useful in pilot-testing the research program's suitability for their institution, and in allowing time to build and consolidate various elective courses before making the commitment to a full, school-wide research requirement. Several successful programs have shown that such an approach can be beneficial 3 .…”
Section: Innovations In Pharmacymentioning
confidence: 99%
“…While the elective approach has certain benefits (highly motivated students and faculty, less burden on institutional resources, faculty, curricular time, logistics) it would result in only a portion of students producing scholarly output. Such an elective program or track may result in an unintentional two-tier system with potential negative perceptions among students 3 . Additionally, student enrollment in research electives is low, less than 10% in most institutions 7 .…”
Section: Criticalmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, different universities have different courses regarding to research activities in the United States [9][10][11].…”
Section: Research Opportunitiesmentioning
confidence: 99%